Hubungan Pengetahuan Ibu dengan Pemberian ASI Eksklusif Pada Bayi di Kabupaten Brebes - Hartini, Sri; Anggraeni, Ria Septiana (JURNAL KESEHATAN TERAPAN, 2024)
In the golden age, the development of the baby's brain experiences approximately 80% growth from birth to the age of 3 years. During this time, babies need enough nutrition, so the government is trying to give babies exclusive breast milk for the first six months of life, which can last up to two years of age. The prevalence of exclusive breastfeeding for 0 to 6 months in Indonesia is 73.97% in 2023, still below the expected national target to achieve the goal of increasing exclusive breastfeeding, which is to reach 80%. This study will examine the relationship between maternal characteristics and exclusive breastfeeding of infants in Brebes Regency in 2024. This type of research involves cross-sectional analytical research. The study population is all mothers who give birth to babies aged 6 to 12 months. in Brebes Regency in 2024. The sampling technique was based on the total sampling technique, which was 45 respondents. Data analysis was used univariate and bivariate analysis with the chi-square test. Based on research results, most people have limited knowledge (56%) and do not provide exclusive breastfeeding (60%). There is a relationship between knowledge about exclusive breastfeeding in babies in Brebes Regency. Efforts for breastfeeding mothers are that the mother must motivate herself to breastfeed her baby by asking the health service provider whether it is permissible to give her baby exclusive breast milk. It is also hoped that health workers can provide more intensive socialization and counseling programs for breastfeeding and pregnant mothers. Health workers can provide health consultations not only at the local Puskesmas, but also outside the Puskesmas such as Posyandu.